2022
DOI: 10.1186/s41205-022-00130-2
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of nanocomposite pills through desktop vat photopolymerization (stereolithography) for drug delivery reasons

Abstract: Background The desktop vat polymerization process or stereolithography printing is an ideal approach to develop multifunctional nanocomposites wherein a conventional solid dosage form is used as a reservoir for compliant administration of drug-loaded nanocarriers. Methods In this study, a nanocomposite drug delivery system, that is, hydrogel nanoparticles of an approved nutraceutical, berberine entrapped within vat photopolymerized monoliths, was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…This work has demonstrated the production of multi-drug therapy (personalized polypills) using SLA 3D printing ( Robles-Martinez et al, 2019 ). Sharma et al (2022) developed a nanocomposite drug delivery system comprising berberine entrapped nanoparticles immobilized in a 3D printed pill, using SLA (Form 2 SLA printer). The berberine entrapped nanoparticles were incorporated into photopolymerizable biocompatible resin, which is composed of PEGDA as a photocrosslinkable monomer.…”
Section: Applications Of Sla In Pharmaceuticals and Medical Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…This work has demonstrated the production of multi-drug therapy (personalized polypills) using SLA 3D printing ( Robles-Martinez et al, 2019 ). Sharma et al (2022) developed a nanocomposite drug delivery system comprising berberine entrapped nanoparticles immobilized in a 3D printed pill, using SLA (Form 2 SLA printer). The berberine entrapped nanoparticles were incorporated into photopolymerizable biocompatible resin, which is composed of PEGDA as a photocrosslinkable monomer.…”
Section: Applications Of Sla In Pharmaceuticals and Medical Devicesmentioning
confidence: 99%
“…Electron microscopy revealed successful entrapment of hydrogel nanoparticles within the pills during the SLA process. Sustained release of berberine from 3D printed pill (Diameter – 7.50 mm and Thickness – 5.00 mm) was achieved ( Sharma et al, 2022 ). Thus, these studies demonstrated the potential of SLA 3D printing technology in developing oral dosage forms (tablets).…”
Section: Applications Of Sla In Pharmaceuticals and Medical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Altering the swelling nature or facilitating the polymeric framework to degrade as a consequence of physical or chemical triggering [59] . Temperature, magnetic fields, pressure, and electric fields provide the physical triggers, while, pH, enzymes, ionic change, and chemical agents act as the chemical triggers [57,60,61] . Drug dissolution, diffusion, the aqueous phase that surrounds that nanogel, and the breaking down of the drug carrier provide as certain other parameters [62] .…”
Section: Drug Loading and Drug Releasementioning
confidence: 99%
“…[13] VPP has been widely used in medical applications due to its ability to print 3D objects with highly complex structural geometry at high accuracy, resolution, and reproducibility in little time than subtractive (traditional) 3D manufacturing. [14][15][16] Generally, four main 3D printing techniques fall under the VPP: stereolithography (SLA), digital light processing (DLP), continuous liquid interface production (CLIP), and daylight polymer printing (DPP). [17] SLA is the oldest form of VPP introduced by Charles Hull in the 1980s.…”
mentioning
confidence: 99%